Hydralazine once daily in hypertension. Issue 6329 (29th May 1982) - Silas, J H; Ramsay, L E; Freestone, S
Abstract : The effects of hydralazine formulation and dose interval were assessed in 20 patients with hypertension well controlled on conventional hydralazine tablets, 100 mg twice daily, in addition to atenolol and a diuretic. The double-blind study used four regimens crossed over in random order at five-week intervals; placebo; conventional hydralazine 100 mg twice daily; conventional hydralazine 200 mg once daily; and slow-release hydralazine 200 mg once daily. Blood pressure and pulse rate were assessed soon after (2.5 +/- 0.9 h) and immediately before taking hydralazine (previous dose: once daily, 26.5 +/- 0.9 h; twice daily, 13.6 +/- 2.0 h). Seventeen patients completed the study. All hydralazine regimens were associated with significant falls in blood pressure. Once-daily treatment with conventional hydralazine was unsatisfactory, as its hypotensive effect waned at 24 h; there was a significant difference between the peak and trough effects on blood pressure and pulse in rapid acetylators. Compared with placebo twice-daily conventional hydralazine and once-daily slow-release hydralazine gave satisfactory control for 24 hours in both rapid and slow acetylators, though the hypotensive effect was larger in the slow acetylators. It is concluded that there is no need to administer hydralazine more than twice daily.